Between Spirituality and Social Context: Unpacking ‘Kidung Rumekso Ing Wengi’ in Javanese Society - Khusniyah, Aziizatul; Cahyandari, Rinova (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to understand how